Atividade física no trabalho, lazer e sono em profissionais da saúde em ambiente hospitalar - Cardoso, Beatriz Medeiros (Universidade Federal de São Carlos, 2024)
Introduction: Healthcare professionals have had their work hours intensified with the arrival of the COVID-19 pandemic. It is important to investigate, through objective measures, occupational physical activity (OPA) and leisure-time physical activity (LTPA), as well as sleep characteristics. Objective: To describe and correlate physical activity at work and during leisure time with sleep quality and duration and musculoskeletal symptoms in healthcare professionals working in a hospital environment, in the context of the COVID-19 pandemic. Methods: Cross-sectional study with 17 healthcare professionals from hospitals in the city of São Carlos (SP). Data collection was performed using an electronic form, containing a sociodemographic questionnaire, the Nordic Musculoskeletal Symptoms Questionnaire (QNSO) and the Pittsburgh Sleep Quality Index (PSQI-Br). In addition, triaxial accelerometers (Axivity AX3) were used to monitor physical activity. The information was analyzed descriptively and through point-biserial correlation analysis. Results: Most participants had low back pain and poor sleep quality. The predominant postures at work and during leisure time were, respectively, sitting (50% and 41%) and standing (30% and 24%). The number of steps was higher during work. There was a negative correlation between light physical activity on non-work days and symptoms in the lumbar spine (r=0.69), feet (r=0.58) and shoulder (r=0.62); and between moderate to vigorous physical activity during leisure time and knee pain (r=-0.68). Conclusion: The practice of physical activity outside the work environment was associated with musculoskeletal symptoms in health professionals. Promoting the practice of physical activity can help in the prevention and control of musculoskeletal symptoms, especially in periods such as the COVID-19 pandemic.
Physical activity at work, leisure and sleep in healthcare professionals in a hospital environment
Keywords: Atividade física; Dor musculoesquelética; Trabalhadores da saúde; Comportamento sedentário; Qualidade do sono; OUTROS